Results from the Tack Optimized Balloon Angioplasty (TOBA) study demonstrate the benefits of minimal metal implants for dissection repair after angioplasty - Bosiers, Marc; Scheinert, Dierk; Hendriks, Jeroen M H; Wissgott, Christian; Peeters, Patrick; Zeller, Thomas; Brodmann, Marianne; Staffa, Robert; TOBA investigators (Journal of vascular surgery, 2016)
OBJECTIVE: The mechanism of angioplasty is disruption of atherosclerotic plaque, which often results in dissections. Dissection after percutaneous transluminal angioplasty (PTA) remains a significant clinical problem and untreated may cause acute occlusion or later restenosis. Stents are used to manage dissections, which is often followed by in-stent restenosis and occasionally stent fracture. Tack (Intact Vascular, Wayne, Pa) implants have minimal metal and low radial force and are specifically designed for dissection repair. This study evaluated Tack implants for treatment of dissections resulting from standard balloon PTA for femoral-popliteal arterial disease. Twelve-month outcomes after Tack treatment of post-PTA dissections are described. METHODS: This prospective, single-arm study evaluated patients with ischemia (Rutherford clinical category 2-4) caused by lesions of the superficial femoral and popliteal arteries. Patients were treated with standard balloon angioplasty, and post-PTA dissections were treated with Tacks. The primary end points were core laboratory-adjudicated device technical success, defined as the ability of the Tack implants to resolve post-PTA dissection, and device safety, defined as the absence of new-onset major adverse events. Patients were followed up to 12 months after implantation. RESULTS: Tacks were used in 130 patients with post-PTA dissections (74.0% ≥ grade C). Technical success was achieved in 128 (98.5%) patients with no major adverse events at 30 days. The 12-month patency was 76.4%, and freedom from target lesion revascularization was 89.5%. Significant improvement from baseline was observed in Rutherford clinical category (82.8% with grade ≤1) and ankle-brachial index (0.68 ± 0.18 to 0.94 ± 0.15; P < .0001). CONCLUSIONS: Tack implant treatment of post-PTA dissection was safe, produced reasonable patency, and resulted in low rates of target lesion revascularization. Tack treatment represents a new, minimal metal paradigm for dissection repair that can safely improve the clinical results associated with PTA.
Keywords: dolní končetina; Popliteal Artery; onemocnění periferních arterií; endovaskulární výkony; cévy - implantace protéz; Humans; průchodnost cév; Metals; lidé středního věku; Female; Aged; Femoral Artery; výsledek terapie; senioři; lidé; kovy; Vascular System Injuries; Prosthesis Design; časové faktory; Retreatment; balónková angioplastika; Lower Extremity; Peripheral Arterial Disease; ženské pohlaví; Male; Middle Aged; cévní protézy; Treatment Outcome; Blood Vessel Prosthesis Implantation; arteria femoralis; Angioplasty, Balloon; arteria poplitea; Endovascular Procedures; protézy - design; mužské pohlaví; prospektivní studie; poranění cév; Blood Vessel Prosthesis; Time Factors; Vascular Patency; opakovaná terapie; Prospective Studies